Rescue Decompressive Craniectomy in Children with Severe Traumatic Brain Injury - Rallis, Dimitrios; Poulos, Panagiotis; Kazantzi, Maria; Kalampalikis, Panagiotis (Journal of Pediatric Intensive Care, 2018)
Decompressive craniectomy (DC) is considered a rescue therapy in patients with traumatic brain injury (TBI) with increased intracranial pressure (ICP). In this retrospective study, we examined the impact of craniectomy on ICP in children with severe TBI and their neurological outcome. A total of 14 patients were enrolled. Peak ICP was significantly lower (31 ± 2.9 to 19 ± 4.6, p < 0.001) and minimum cerebral perfusion pressure (CPP) higher (41 ± 10.5 to 58 ± 11.4, p < 0.001) postcraniectomy. The survival rate was 71%. However, 57% of our cohort had a poor neurological outcome at 6 months postinjury. In conclusion, although rescue DC was effective in controlling ICP and CPP, the long-term neurological outcome remained poor.
Keywords: traumatic brain injury; pediatric; craniectomy